Collaboration as a foundation for modern education (as exemplified by primary general education) - Nekhoroshikh, Natalya A. (2021)
The author aims to study the implementation of the theoretical analysis of cooperation as the most fruitful fundamental basis of education for achieving high results, identifying the subjective and objective circumstances of the influence of the cooperation skills development level on the success of teaching younger students. An integrated approach to studying the problem was the leading method that made it possible to consider this issue in three aspects: from the side of primary schoolchildren, primary school teachers and principals, and head teachers of educational institutions. The author identified socio-pedagogical and psychological conditions that ensure an increase in the performance of younger students in the educational process based on ideas of cooperation, as well as factors that inhibit the development of their cooperation, which negatively affects academic performance. It has been proven empirically that the organization of the educational process in primary school based on the ideas of cooperation, when students are the subject of educational relations, contributes to their achievement of higher learning outcomes. The significance of the research results obtained is to prove the positive consequences of building the educational process based on cooperation.